Minor Environmental Virtues - Dzwonkowska, Dominika (Studia Ecologiae et Bioethicae, 2016)
Environmental virtue ethics is an answer to the deficiency of normative ethical traditions in dispute on environmental crisis. Usually a discussion on virtue concentrates on cardinal virtues and vices providing various catalogues of the character traits that support or hinder our moral development. However, cardinal virtues and vices do not exhaust all of the debate over character; discussions on environmental character can include virtues that are not classified as cardinal but can be equally important. These are so called minor virtues; they are not on the first front of environmental virtue discussion but can play a crucial role in forming the right attitude towards the natural world. This paper analyzes so called minor environmental virtues and their role in forming environmental character.